Anthropometric profile, nutritional status and body composition in schoolchildren who practice and do not practice futsal - Lourenço, Isaac de Sousa (2025)
This study aimed to measure the anthropometric variables of schoolchildren who practice and do not practice futsal, evaluating their nutritional status and body composition. The research was conducted between February and December 2023 with 851 students from schools in Anapurus, Brejo, and Buriti, Maranhão. The sample was divided into 250 futsal players and 601 non-players. Variables such as total body mass (TBM), height, BMI, body fat percentage (BFP), fat mass (FM), and fat-free mass (FFM) were collected, along with the classification of nutritional status and body composition. The statistical analysis included the Student's t-test for group comparisons. The results indicated that, although the differences in anthropometric characteristics between futsal players and non-players were not statistically significant (p<0.05), futsal players showed a more balanced body composition profile, with lower body fat percentage and higher lean mass. Furthermore, futsal players had a lower prevalence of malnutrition and overweight. In conclusion, although futsal practice did not show significant differences in anthropometric variables, it is associated with a healthier body composition and may be beneficial in preventing nutritional problems. This suggests that regular futsal practice contributes positively to the overall health of schoolchildren.